Effect of adjuvants on the retention of insecticide spray on cucumber and pea foliage - Gaskin, R.E.; Murray, R.J.; Krishna, H.; Carpenter, A. (New Zealand Plant Protection, 2000)
Spray additives are often used to enhance the efficacy of agrochemicals in the management of pests and diseases in vegetables but their effects can vary widely and are not fully understood This study investigated the effects of adjuvants on the retention of a systemic insecticide spray on two contrasting plant species Adjuvants provided no benefits on easytowet cucumber foliage particularly with high volume application On waterrepellent pea foliage retention of spray was enhanced by adjuvants (P